Changing metabolic functions in experimental animals after introduction of the xenobiotic, immunotropic drug and probiotic - Zvyagintseva, O; Klimova, E; Lavinska, O; Lenkevich, A (Annals of Mechnikov's Institute, 2020)
The aim of the study was to evaluate in vivo changes in metabolic and barrier function of the resistance factors (activity of enzymes of neutrophils, the efficiency of phagocytosis), some biochemical parameters (concentration of ceruloplasmin and haptoglobin) and proliferate activity in vitro cells after introduction of copper sulfate, probiotics and immunostimulant "Fungidol" the experimental animals. Material and methods. The in vivo experiments were performed on 6-month-old male rats of Wistar line. Identified the following groups: group 1 - control animals, which were intraperitoneally injected with saline (n = 5); group 2 - animals that were administered saline per os and 48 hours a solution of copper sulphate intraperitoneally (n = 5); group 3 - animals, which were injected with immunotropic drug "Fungidol" per os and 48 hours a solution of copper sulphate intraperitoneally (n = 5); group 4 animals, which were injected with a solution of probiotics per os and 48 hours a solution of copper sulphate intraperitoneally (n = 5). As a probiotic used capsules firm Yogurt that contains active Lactobacillus acidophilus, Lactobacillus rhamnosus, Streptococcus thermophillus, Lactobacillus bulgaricus. The concentration of haptoglobin and ceruloplasmin were determined spectrophotometrically. Oxygen-dependent metabolism of neutrophils was investigated by microscopy according to their ability to absorb nitroblue tetrazolium (NBT-test) and restore it to deformazione in the form of granules blue color under the influence of superoxide anion, which is formed in the NADP-oxidase reaction, initiating the process of stimulation of phagocytosis (NBT-test). To determine the barrier function of phagocytic cells by light microscopy to evaluate the activity of phagocytosis of neutrophilic granulocytes with subsequent determination of phagocytic index, phagocytic number and the index of completeness of phagocytosis. As a microbial agent used is a suspension culture of Saccharomyces cerevisiae. The peripheral blood leukocytes were cultured according to the method of Hereford in medium 199 with the addition of fetal calf serum in the absence and in the presence of T-cell mitogen – phytohemagglutinin. Results and discussion. In all studied groups (introduction of the xenobiotic, "Fungidol", probiotic experimental animals revealed a significant increase in the concentrations of ceruloplasmin and haptoglobin on the average in 1,5 times in comparison with the control, indicating the development of the inflammatory process after the toxic action of copper sulphate. During administration of sulphate of copper, the experimental animals showed a reduction in the index of completion of phagocytosis, indicating a failure of the process of endocytosis of bacterial antigens and reduced stimulation index due to the low activity of NADP-oxidase system of phagocytes. The introduction of xenobiotic animals was increased 1,2 times compared with the control (23,33±1,38) % the number of transformed cells in the background of mitogenic inducer of cell proliferation. The proliferative activity of hemolytic after the joint action of the xenobiotic and immunotropic drug in cell culture with the mitogen was the highest and exceeded 1,5 times control (23,33±1,38)%. After the introduction of copper sulfate and probiotic proliferative activity of hemolytic was also significantly higher spontaneous. Introduction biologic response modifier substance to a greater extent than probiotics stimulate a protective immune processes aimed at combating the negative effect of the xenobiotic. Conclusion. Thus, the introduction of copper sulfate launches in animals a cascade of reactions aimed at the disruption of homeostasis. It is a violation of various physiological processes of digestion, respiration, cell differentiation, water-salt metabolism, metabolism of carbohydrates, proteins, lipids, detoxification of exogenous substrates and metabolites, production of biologically active compounds. Introduction immunostimulant and probiotics, in varying degrees, led to activation of protective mechanisms under the action of stress factors aimed at the adaptation and translation of the body into a new functional state.